GUBERNAMENTALIDAD NEOLIBERAL Y EDUCACIÓN UNIVERSITARIA EN EL PERÚ. UN PROGRAMA DE PROFESIONALIZACIÓN DE ADULTOS EN UNA UNIVERSIDAD DE LIMA - YALLE QUINCHO, Omar (2023)
This article addresses from the concept of governmentality neoliberal, anduniversity education in Peru, the case study of the Certified Work ExperienceProgram in a private university in Lima, to learn about the training of professionalswho form and what perspectives your students have. Methodologically, thestudy is qualitative supported by interviews and directed questionnaires. Itis concluded that the Neoliberal governmentality is a concept that allowsus to analyze education university, as a means of training the student of theorganization of the company and the entrepreneurial subject.